Potret Aktivitas Makan dalam Leksikon Jawa dan Nilai Filosofi - M. Suryadi (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
The purpose of this study is to prove that there is a relationship between eating activities and the behavior of coastal Javanese in Semarang City. This correlation study involves the relationship of the form of the lexicon to the concept of the lexicon and the value of Javanese philosophy. Research Location in the Central Java Coastal Region, a locus of research in the city of Semarang. This type of research is descriptive qualitative. Data collection methods used were observation, documentation, and active participation through in-depth interviews. The analytical method used is the lexicon mapping based on the form of unit - cultural values - references. The consideration used to map the lexicon is the cultural value in Javanese tradition. The theory used is the reconstruction of the lexicon in the meaning group of eating activities. The findings of the study are the self-identity of the eating activity lexicon has a correlation with Javanese human behavior, especially in socializing with the community. The lexicon of eating activity, preserving the values of Javanese culture in contact with politeness.